2010
DOI: 10.1016/j.foodchem.2009.07.050
|View full text |Cite
|
Sign up to set email alerts
|

Production and refinement of oil from carp (Cyprinus carpio) viscera

Abstract: a b s t r a c tCarp viscera oil can be obtained by both ensilage and fishmeal processes. This study examined the refinement of carp (Cyprinus carpio) oils obtained by both processes, and compared crude, neutralised, bleached, winterised and deodorised oils' characteristics and lipid profiles. Refined oils obtained by the two processes did not present significant difference (p > 0.05) for Lovibond colour, free fatty acids, and thiobarbituric acid values. The major fatty acids identified in the carp crude, bleac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
96
0
14

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(141 citation statements)
references
References 31 publications
16
96
0
14
Order By: Relevance
“…The refining of crude fish oil normally includes the processes of degumming, neutralization, drying, bleaching, deodorization and winterization (Crexi et al, 2010). In this study, the performed a semi-refining were included, the neutralization (chemical refining) and bleaching (physical refining) of the addition of activated clay, according to American Dil Chemists Society (2002).…”
Section: Refining Of the Special Fish Oilmentioning
confidence: 99%
See 1 more Smart Citation
“…The refining of crude fish oil normally includes the processes of degumming, neutralization, drying, bleaching, deodorization and winterization (Crexi et al, 2010). In this study, the performed a semi-refining were included, the neutralization (chemical refining) and bleaching (physical refining) of the addition of activated clay, according to American Dil Chemists Society (2002).…”
Section: Refining Of the Special Fish Oilmentioning
confidence: 99%
“…It is considered that the profiles of methyl fatty acids from residues of refined special fish oil and hydrolyzed special fish oil were significant different (p<0.05) for the two refining processes and hydrolysis, the latter with the highest amount of polyunsaturated. The main quantities of the following fatty acids were identified: saturated fatty acids C16:0 (palmitic acid), monounsaturated fatty acid (MUFA) and PUFAs (C18:1n-9 or oleic acid, C20:5n3 or EPA, C22:6n3 or DHA and C20:4n-6 or arachidonic), whose characterization was assigned to freshwater fish oil (Guler et al, 2008;Crexi et al, 2010). The most abundant fatty acids were arachidonic, eicosapentaenoic, docosahexaenoic and oleic acid.…”
Section: Physical-chemical Characterizationmentioning
confidence: 99%
“…These studies showed that p-anisidine value of both conditions was in the range to standard by FDA GRAS which was below 20 mmol/kg [27,28,30] and 4-60 mmol/kg [31]. P-anisidine value gained by crude oil from carp (Cyprinus carpio) viscera was 10.3 ± 0.3 [32] a bit higher compared to treat waste with microwave pretreatment. Iodine value for oil extraction of catfish by using microwave pretreatment was 75.10 below than typical iodine values for fish oil, 120-180 [33] and iodine value by Bimbo [31].…”
Section: Icmce 2015mentioning
confidence: 99%
“…Like in most other fish the polyunsaturated fatty acids were dominated by two members of the n-3 family, that is C20:5n-3 (eicosapentaenoic acid or EPA) and C22:6n-3 (docosahexaenoic acid or DHA) 16 . Crexi et al 5 stated that the palmitic acid is a saturated fatty acid composition of the dominant with 50% of the total saturated fatty acids. Oleic acid is one of unsaturated fatty acids that is the most common and are precursors for production of PUFAs 2 .…”
Section: Fatty Acid Profilementioning
confidence: 99%